Examining the talent selection determinants of ultimate frisbee players selected into a national youth team - Connor, J. D.; Berkelmans, D.; Doma, K. (International Journal of Sports Physiology and Performance, 2023)
Purpose: The purpose of the study was to examine whether various athletic performances, anthropometric measures, and playing experience differentiate selected and nonselected ultimate Frisbee players trialing to compete in the world championship. Methods: Forty-three Australian male ultimate Frisbee players (age = 21.2 [1.2] y; height = 1.7 [6.8] m; body mass = 69.7 [8.2] kg; playing experience = 3.5 [1.5] y) participated in a 30-m sprint test, single-leg run-up jump approach (both left [JumpLL], and right leg [JumpRL]) and a stationary bilateral vertical jump (JumpBIL), and change-of-direction speed test. Following a selection camp, players were subdivided according to their selection or nonselection into the team. Results: A multivariate analysis of variance revealed that height, 10-m sprint time, acceleration, JumpLL, JumpRL, and JumpBIL were significantly greater for selected players than nonselected players (P < .05). Area under the curve (AUC) was greatest for JumpRL (AUC = 79%; optimal cutoff value of 37.5 cm, sensitivity and specificity values of 77% and 71%, respectively), JumpLL (AUC = 74%; optimal cutoff 38.5 cm, sensitivity and specificity values 77% and 77%, respectively), and JumpBIL (AUC = 78%; optimal cutoff value of 40.5 cm, sensitivity and specificity values 71% and 79%, respectively). The largest AUC (AUC = 81%; 95% CI 0.66-0.97; P = .001) was found when combining the explanatory variables that demonstrated moderate to large effect sizes (ie, height, playing experience, 10-m sprint, acceleration, JumpLL, JumpRL, and JumpBIL), with sensitivity of 93% and specificity of 71%. Conclusion: These athletic performance and anthropometric characteristics differentiating selected and nonselected players may help inform targeted training and player-development strategies.